DINAMIKA GENDER DAN PERAN PEREMPUAN DALAM EKONOMI KELUARGA - Mujahidah, Mujahidah (AL-MAIYYAH, 2015)
This paper describes the dynamics and discourse of gender issues that have successfully penetrated hard paternalistic culture. Gender discourse takes attention a lot of various parties, and even have become mainstreaming which significantly influence social changes. Gender issues have broken every corner of thought and life by putting "women" as an object of discussion. The central theme is equality between men and women in any cases. This issue, with all of its problems became a very interesting discourse discussed by intellectuals over the world. Struggle and gender movement has ripped off peopleâs perception that women are weak creatures and become the second in social reality. In pragmatic area, gender understanding give impact on relationship between men and women as husband and wife. Gender awareness has opened up equality of right and obligation between them in running domestic life. The responsibility for the protection, safety, prosperity, and living for families which used to be on menâs shoulder, it is played also by women.